Personal Characteristics and their Impact on the Professional Judgments Quality of the External Auditor: A Field Study -Field Study- - Nashwan, Iskandar (Jordan Journal of Business Administration, 2019)
This study aimed to determine the impact of personal characteristics (honesty, neutrality and independence, professional and technical efficiency, dignity and professionality and full privacy) on the quality of professional judgments of the external auditor. In order to achieve that aim, the descriptive analytical method was used because of its suitability for this type of study. The study tool was a questionnaire designed for this purpose, which was applied to the study sample of (114) external auditors in the Gaza Strip. Moreover, several statistical equations were used to process the results, such as arithmetic means and standard deviations. After analyzing the results, the researcher reached a number of results, the most important of which is that there is a statistically significant impact of personal characteristics on the quality of professional judgments of external auditors. Professional and technical efficiency had the greatest impact. Furthermore, there is a statistically significant impact of these characteristics on the quality of professional judgments due to the variable of academic qualification, in favor of those who hold postgraduate degrees and due to the variable of correlation with international auditing offices for the benefit of associates. There is no statistically significant impact of these characteristics on the quality of professional judgments according to the variables of years of experience and type of office. Based on the results of the study, the researcher presented a number of recommended, the most important of which are to encourage external auditors to follow noble moral values, especially the secretariat required in the completion of their work, as well as to build connections with associations, bodies and professional organizations interested in professional affairs in order to strengthen the independence of auditors to perform their work without any pressure, thus enabling them to issue rational professional judgments.